Pengaruh Penganggaran Terhadap Profitabilitas UMKM : Studi Kasus Pada Warung Pentol Ndower Solo di Pasar MMTC Medan - Lokot Muda Harahap; Maya Martiza Sari; Hasiandra Simanjuntak; Putri Sandrina Sitompul; Anita Saragih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of budgeting on profitability. In this research we will carry out market analysis so that we can find out how much influence company budgeting has on profitability. In this research we used quantitative methods with descriptive and explanatory approaches. The research conducted used the dependent variable of profitability and the independent variable, namely budgeting, to show how much budgeting is related to profitability. The research instrument is: We directly carried out an analysis which we carried out for 3 months so that we could find out the profits of the MSMEs that we analyzed. The result is that from the analysis we have carried out, SMEs experience fluctuations caused by unexpected things such as fasting, but from the analysis we have carried out the company makes large profits. With this research, it is hoped that it will be able to help other MSMEs in developing their business because by implementing budgeting in business, MSMEs are able to run their businesses effectively and efficiently.